2019
DOI: 10.1038/s41467-019-10271-4
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of antibiotic sensitivity and biofilm formation in Pseudomonas aeruginosa by interspecies signal analogues

Abstract: Pseudomonas aeruginosa , a significant opportunistic pathogen, can participate in inter-species communication through signaling by cis -2-unsaturated fatty acids of the diffusible signal factor (DSF) family. Sensing these signals leads to altered biofilm formation and increased tolerance to various antibiotics, and requires the histidine kinase PA1396. Here, we show that the membrane-associated sensory input domain of PA1396 has five transmembrane helices, two of which are req… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 43 publications
0
28
0
Order By: Relevance
“…For example, in P. aeruginosa, the QS system has two signaling systems: lasl/lasR and rhlI/rhlI. The lasl/rhlI and lasR and rhlR genes encode different signal molecule synthetases and signal molecule receptors, respectively [77,78]. Signal molecules increase in secretion as the density of bacteria increases.…”
Section: Regulation Of Bacterial Biofilm Formation By Qsmentioning
confidence: 99%
“…For example, in P. aeruginosa, the QS system has two signaling systems: lasl/lasR and rhlI/rhlI. The lasl/rhlI and lasR and rhlR genes encode different signal molecule synthetases and signal molecule receptors, respectively [77,78]. Signal molecules increase in secretion as the density of bacteria increases.…”
Section: Regulation Of Bacterial Biofilm Formation By Qsmentioning
confidence: 99%
“…In one dispersal study, Rahmani-Badi et al (2015b) have identified protein transcription changes occurring in P. aeruginosa upon stimulation with C2DA, identifying a cluster of genes implicated in sensing and responding to fatty-acid signals, including regulation of pathogenicity factor (rpf) proteins. It has also been shown that the histidine kinase PA1396 in P. aeruginosa is a major factor in DSF function; certain DSF analogs are able to block the ability of PA1396 to autophosphorylate, which subsequently reduces biofilm formation and antibiotic tolerance both in vitro and in vivo ( An et al, 2019 ). Previous research has also demonstrated that C2DA increased membrane permeability of P. aeruginosa and S. aureus ( Masters et al, 2016 ), which may occur by substitution of membrane phospholipids by fatty acid or by stimulating proton-motive force at the membrane ( Meylan et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…If indeed potential cell-cell communication via quorum sensing mediates the formation of filamentous cells 7,33,34 , we reasoned that variances in distance between Au disks should affect this process. Following this idea, the formation of filamentous cells was monitored via fluorescence imaging of cells clusters separated over various distances.…”
Section: Spatial Proximity and Density Of Bacterial Clusters Induce Cell Elongationmentioning
confidence: 99%
“…Bacteria have evolved diverse surface adhesion mechanisms to enable biofilm formation on biotic and abiotic substrates in a variety of natural, medical, and industrial settings [1][2][3] . The virulence of pathogenic bacteria strongly depends on their capability to attach to biotic surfaces and form multicellular assemblies [4][5][6][7][8] . Such pathogenic biofilms are highly resistant to diverse antimicrobial compounds due to their encapsulation within a matrix of hydrated extracellular polymeric substances (EPS) 7,9 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation